2021
DOI: 10.1002/adma.202007293
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Assembled Programmable Nanomedicine As In Situ Cancer Vaccine for Cancer Immunotherapy

Abstract: Using nanotechnology for improving the immunotherapy efficiency represents a major research interest in recent years. However, there are paradoxes and obstacles in using a single nanoparticle to fulfill all the requirements in the complicated immune activation processes. Herein, a supramolecular assembled programmable immune activation nanomedicine (PIAN) for sequentially finishing multiple steps after intravenous injection and eliciting robust antitumor immunity in situ is reported. The programmable nanomedic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
95
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 135 publications
(96 citation statements)
references
References 48 publications
0
95
1
Order By: Relevance
“…Many studies reported that Poly (amidoamine) (PAMAM) is pH-sensitive because of its loose structure under weakly acidic conditions [ 32 , 33 ], which could be exploited to trigger drug release, and thus could be widely used for responsive release in acidic environments. In addition, PAMAM is an excellent nanosized platform for drug delivery in numerous applications [ [34] , [35] , [36] ] because of its specific structure, such as the interior hydrophobic region, a large number of end amino groups, and narrow size distribution [ [37] , [38] , [39] , [40] , [41] ]. Moreover, many bacterial enzymes (e.g., esterase, lipase, and gelatinase) exist in dental plaque [ 29 , 42 , 43 ] and can be exploited to achieve enzyme-mediated drug release.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies reported that Poly (amidoamine) (PAMAM) is pH-sensitive because of its loose structure under weakly acidic conditions [ 32 , 33 ], which could be exploited to trigger drug release, and thus could be widely used for responsive release in acidic environments. In addition, PAMAM is an excellent nanosized platform for drug delivery in numerous applications [ [34] , [35] , [36] ] because of its specific structure, such as the interior hydrophobic region, a large number of end amino groups, and narrow size distribution [ [37] , [38] , [39] , [40] , [41] ]. Moreover, many bacterial enzymes (e.g., esterase, lipase, and gelatinase) exist in dental plaque [ 29 , 42 , 43 ] and can be exploited to achieve enzyme-mediated drug release.…”
Section: Introductionmentioning
confidence: 99%
“…Natural killer (NK) cell membrane 119 and myeloid-derived suppressor cell membrane 174 are useful to coat nanoparticles for enhanced PDT to promote ICD and activate immune responses that suppress significantly both in situ and metastatic tumors. In situ immunotherapy requires multiple steps, to address this issue, a recent study reported a nanomedicine strategy for programmable immune activation driven by the high level of reactive oxygen species induced by supramolecular assembled nanoparticle in the tumor microenvironment 175 . Release of drug and CpG/PAMAM led to the exposure of tumor antigen and APC activation, and subsequent antitumor immune responses.…”
Section: Nanovaccines For Diseases Prevention and Treatmentsmentioning
confidence: 99%
“… 7 , 8 , 9 Synthetic oligodeoxynucleotides (ODNs) comprised CpG motifs are found to stimulate similar immunomodulatory responses and display a great potential in the therapy of infection, cancer, or allergy. 5 , 10 , 11 However, free CpG ODNs are susceptible to nuclease cleavage and have poor cell permeability due to their anionic and hydrophilic properties. 12 , 13 , 14 , 15 , 16 Although phosphorothioate modification of the backbone can confer the resistance to nuclease degradation, it concurrently increases the cytotoxicity and thereby limits the clinical utilization of CpG ODNs.…”
Section: Introductionmentioning
confidence: 99%